2004
DOI: 10.4315/0362-028x-67.5.884
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inactivation of Escherichia coli O157:H7 in Bovine Rumen Fluid by Caprylic Acid

Abstract: The antibacterial effect of caprylic acid (35 and 50 mM) on Escherichia coli O157:H7 and total anaerobic bacteria at 39 degrees C in rumen fluid (pH 5.6 and 6.8) from 12 beef cattle was investigated. The treatments containing caprylic acid at both pHs significantly reduced (P < 0.05) the population of E. coli O157:H7 compared with that in the control samples. At pH 5.6, both levels of caprylic acid killed E. coli O157:H7 rapidly, reducing the pathogen population to undetectable levels at 1 min of incubation (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…It is evident that caprylic acid can have anti-microbial activity, similar to pre-or probiotics, against a wide range of microorganisms such as Salmonella enteritidis in chicken caecal contents (Vasudevan et al, 2005;Skrivanová et al, 2006;Solis de los Santos et al, 2008;Solis de los Santos et al, 2009); E.coli in bovine rumen fluid (Annamalai et al, 2004); and weaning rabbits (Skrivanová et al, 2008;Skrivanová et al, 2009). On the other hand, the Yucca saponins also have antibacterial properties, but exert marginal effect on the Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is evident that caprylic acid can have anti-microbial activity, similar to pre-or probiotics, against a wide range of microorganisms such as Salmonella enteritidis in chicken caecal contents (Vasudevan et al, 2005;Skrivanová et al, 2006;Solis de los Santos et al, 2008;Solis de los Santos et al, 2009); E.coli in bovine rumen fluid (Annamalai et al, 2004); and weaning rabbits (Skrivanová et al, 2008;Skrivanová et al, 2009). On the other hand, the Yucca saponins also have antibacterial properties, but exert marginal effect on the Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, caprylic acid was reported to have anti-microbial activity against a wide range of microorganisms such as Salmonella enteritidis in chicken caecal contents (Vasudevan et al, 2005;Skrivanová et al, 2006;Solis de los Santos et al, 2008), and Escherichia coli 0157:H7 in bovine rumen fluid (Annamalai et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Broilers fed the CAY100 diet exhibited reduced E. coli counts compared with the NC diet, which is in agreement with Wang and Kim (2011), who suggested that supplementation of the laying hen diet with 120 mg/kg caprylic acid and 120 mg/kg yucca extract significantly decreased excreta E. coli both at the three and five week stages. Moreover, several researchers have claimed that caprylic acid has anti-microbial activity against a wide range of microorganisms such as E. coli, Campylobacter jejuni and Salmonella enteritidis in poultry and bovines (Annamalai et al 2004 (Wang et al 2000a;Cheeke et al 2006;Wang and Kim 2011). Thus, CAY supplementation may improve gut health and subsequently improve immunity and growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of CA (5 g/kg) to a diet for piglets increased (P < 0.05) weight gain versus the basal diet (Marounek et al 2004). Recently, caprylic acid was reported to have anti-microbial activity against a wide range of microorganisms such as Salmonella enteritidis and Campylobacter jejuni in chicken caecal contents (Vasudevan et al 2005;Skrivanova et al 2006; Solis de los Santos et al 2008;Wang and Kim 2011) and Escherichia coli 0157:H7 in bovine rumen fluid (Annamalai et al 2004). The use of Yucca schidigera (YS) extract in poultry feed is a good alternative to improve feed efficiency and increased production (Ayasan et al 2005).…”
mentioning
confidence: 99%
“…Therefore, interventional strategies implemented at the farms for reducing C. jejuni counts in the chicken intestinal tract are critical for delivering a microbiologically safer product. Fatty acids, especially medium chain fatty acids, were found to have antimicrobial properties for a wide range of microorganisms (2,3,16,19,24,27). Recently, Thormar and coworkers (26) reported that monocaprin, the monoglyceride of capric acid, was effective in killing significant populations of C. jejuni in chicken feed.…”
mentioning
confidence: 99%